Developmental responses of Cryptolaemus montrouzieri to heavy metals transferred across multi-trophic food chain. (August 2018) - Sang, Wen; Xu, Jing; Bashir, Muhammad Hamid; Ali, Shaukat
Abstract: The current studies were carried out to observe the variations in development, biology and life table parameters of ladybird beetle, Cryptolaemus montrouzieri, feeding on pink hibiscus mealybug ( Dysmicoccus neobrevipes ) contaminated with heavy metals (cadmium, lead, and nickel) bio-transferred across a multi-trophic chain. The developmental time required for immature life stages (1st, 2nd, 3rd, 4th instar nymphs, pupae) and total developmental period (egg-adult) differed significantly among different heavy metal treatments and control. The accumulated survival rate of C . montrouzieri immature life stages also differed significantly among different heavy metal treatments and control. Different parameters of adult female biology (Pre-oviposition period, fecundity, female longevity) were adversely affected by different heavy metals. Life table analysis revealed that all the heavy metals caused significant reduction in net reproduction rate (R0 ) and intrinsic rate of increase (r) while the mean generation time (T) and doubling time (Dt ) were significantly higher than control. The results obtained provide possible insight into the implications of heavy metals on the population dynamics of insect predator ( C . montrouzieri ) in a multi-trophic food chain. However, further research is required on genetic as well as physiological processes involved in the regulation of growth and development of C . montrouzieri. Graphical abstract: Image Highlights: Effects of heavy metals on biology and life table of Cryptolemus montrouzieri. The developmental periods of C. montrouzieri were affected by heavy metals. The age stage specific survival rates were also influenced by heavy metals. Female longevity and fecundity were reduced by different heavy metals. All the heavy metals significantly affected different life table parameters.